Paired electrolysis-enabled nickel-catalyzed enantioselective reductive cross-coupling between α-chloroesters and aryl bromides - Dong Liu; Zhao-Ran Liu; Zhen-Hua Wang; Cong Ma; Simon Herbert; Hartmut Schirok; Tian-Sheng Mei (Nature Communications, 2022)
Precise matching of reaction rate and electric potential of electrodes in paired electrolysis is challenging. Here, the authors develop paired-electrolysis-enabled nickel-catalyzed enantioselective reductive cross-coupling of α-chloroesters and aryl bromides.